1998
DOI: 10.1107/s0907444997016806
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the C-Type Lectin Carbohydrate Recognition Domain of Human Tetranectin

Abstract: Tetranectin (TN) is a C-type lectin involved in fibrinolysis, being the only endogenous ligand known to bind specifically to the kringle 4 domain of plasminogen. TN was originally isolated from plasma, but shows a wide tissue distribution. Furthermore, TN has been found in the extracellular matrix of certain human carcinomas, whereas none or little is present in the corresponding normal tissue. The crystal structure of full-length trimeric TN (2.8 A resolution) has recently been published [Nielsen et al. (1997… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 12 publications
(22 reference statements)
1
18
0
Order By: Relevance
“…The CTLD structural units share a common structural core and serve as a scaffold to hold in place the more individual loop regions that line the ligand-binding site [12]. Diversity can be introduced by randomization of the sequences of individual loops, creating a much larger pool of potential binders than can be displayed on phage.…”
Section: Tetranectinsmentioning
confidence: 99%
“…The CTLD structural units share a common structural core and serve as a scaffold to hold in place the more individual loop regions that line the ligand-binding site [12]. Diversity can be introduced by randomization of the sequences of individual loops, creating a much larger pool of potential binders than can be displayed on phage.…”
Section: Tetranectinsmentioning
confidence: 99%
“…The Plg kringle-4-binding site is located within the domain encoded by exon 3 [13], which encodes a domain similar with the carbohydrate recognition domains (CRDs) of the C-type lectin superfamily [14]. TN exhibits pronounced structural similarity to both the neck region and the CRD of the collectins, and binds Ca# + in a similar way [15,16]. The binding to Plg kringle 4 has been shown to involve amino acid residues near and within the Ca# + -binding site 2 ; accordingly, Plg kringle 4 and Ca# + are competitive ligands for the CRD domain of TN [13].…”
Section: Introductionmentioning
confidence: 99%
“…Solution of the crystal structures of recombinant TN (Nielsen et al, 1997) and of the CRD domain of TN (Kastrup et al, 1998) showed that the structural element governing TN trimerisation is a short ␣-helical coiled coil and that the framework structure of TN CRD is almost super-imposable on framework structures of several other CRD domains, except in the loops that define the two calcium binding sites and the putative sugar binding site. Solution of the crystal structures of recombinant TN (Nielsen et al, 1997) and of the CRD domain of TN (Kastrup et al, 1998) showed that the structural element governing TN trimerisation is a short ␣-helical coiled coil and that the framework structure of TN CRD is almost super-imposable on framework structures of several other CRD domains, except in the loops that define the two calcium binding sites and the putative sugar binding site.…”
Section: Introductionmentioning
confidence: 99%